Comparison of Treatment Outcomes Following Either Prefrontal Cortical-only or Dual-site Repetitive Transcranial Magnetic Stimulation in Chronic Tinnitus Patients: A Double-blind Randomized Study. Issue 2 (February 2017) - Noh, Tae-Soo; Kyong, Jeong Sug; Chang, Mun Young; Park, Moo-Kyun; Lee, Jun-Ho; Oh, Seung-Ha; Kim, June Sic; Chung, Chun Kee; Suh, Myung-Whan
Abstract : Objectives: We evaluated treatment outcomes following single-site repetitive transcranial magnetic stimulation (rTMS) in the dorsolateral prefrontal cortex (DLPFC) and dual-site rTMS in the auditory cortex (AC) and DLPFC (AC + FC). Study Design and Patients: This prospective randomized double-blind trial initially included 19 patients with chronic tinnitus and 17 of these patients received rTMS on the left AC and left DLPFC or only the left DLPFC. The subjects were randomly allocated to either the dual-site rTMS (AC + FC) protocol (Group 1, n = 9) or the singlesite rTMS (DLPFC) protocol (Group 2, n = 8). Group 1 received daily treatments with 2, 000 pulses applied to the AC and 1, 000 pulses applied to the DLPFC for 4 days (total of 12, 000 pulses) and Group 2 received daily treatments with 3, 000 pulses applied the DLPFC for 4 days (total of 12, 000 pulses). Main Outcome Measures: The severity of tinnitus was assessed before rTMS treatment using the Tinnitus Handicap Inventory (THI) and the self-rated Visual Analog Scale. These measures were used to determine the awareness, loudness, annoyance, and effects of tinnitus on daily life at 1, 2, 4, and 12 weeks after treatment. Results: The improvement in THI score was significantly better in Group 1 than in Group 2, even after controlling for the between-group differences in pretreatment THI score. In terms of psychological factors, Group 1 exhibited significant improvements in scores on the State-Trait Anxiety Inventory (STAI) for both state anxiety (STAI-X1) and trait anxiety (STAI-X2) at 12 weeks posttreatment and scores on the Pittsburgh Sleep Quality Index at 4 weeks posttreatment. Group 2 showed an improvement in only the STAI-X2 score at 12 weeks posttreatment. Conclusions: The rTMS protocol effectively suppressed tinnitus in the dual-site rTMS (AC+FC) group but not in the single-site rTMS (DLPFC) group. Although recent evidence has shown that non-auditory cortices in the tinnitus network play an important role in the generation of tinnitus, our findings indicate that rTMS on non-auditory cortical sites alone may not be sufficient for treatment. Thus, dual-site rTMS in the AC and DLPFC may be preferable for controlling this condition.